Teachers’ Perceptions about Change in Times of Pandemic - Cardona, Liliana María (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The pandemic caused by Covid-19 has transformed all sectors. In education, challenges are assumed to give continuity to the processes in a virtual way, however, until now they do not transcend the use of technological tools that are far from becoming models of virtual education. This work was interested in knowing the perceptions of teachers about the change generated by the pandemic, which guides the design of training plans in institutions. In the same way, it presents a change management model that can be adapted to specific situations and needs, with which it is intended to help managers of educational institutions to properly lead the change the challenges they face. For this, an online questionnaire was applied to teachers of educational institutions of all levels. The results show the need to implement learning models in virtual environments, as well as the urgency of dealing with the anguish of teachers at this time of transition, through the facilitating strategies for change that are presented in the proposed model.